2013
DOI: 10.1128/jcm.01161-13
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Activation as a Versatile Assay Platform for Detection of Cytotoxic Bacterial Toxins

Abstract: Pathogenic bacteria produce several virulence factors that help them establish infection in permissive hosts. Bacterial toxins are a major class of virulence factors and hence are attractive therapeutic targets for vaccine development. Here, we describe the development of a rapid, sensitive, and high-throughput assay that can be used as a versatile platform to measure the activities of bacterial toxins. We have exploited the ability of these toxins to cause cell death via apoptosis of sensitive cultured cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…It has previously been shown that PE exploits several host proteins for its binding to and entry into host cells 5 and initiates programmed cell death by inducing activities of host caspase-3, -6, and -7 6 . We investigated whether known mutations in host proteins exploited by PE associate with altered cytotoxicity of the toxin in cells from tissues that are naturally attacked by this toxin.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that PE exploits several host proteins for its binding to and entry into host cells 5 and initiates programmed cell death by inducing activities of host caspase-3, -6, and -7 6 . We investigated whether known mutations in host proteins exploited by PE associate with altered cytotoxicity of the toxin in cells from tissues that are naturally attacked by this toxin.…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-3/7 enzyme activity assays (apopain and CPP32 assays) are fluorescence-based test systems designed for quantification of apoptosis [57,58]. Different probes have been developed to quantify caspase activity, including Förster resonance energy transfer (FRET)-based systems [59] and rhodamine-110 labeled substrates [60].…”
Section: Apoptosismentioning
confidence: 99%
“…2b) is likely a result of a polygenic inheritance model, consistent with evidence that multiple host proteins mediate PE lethality 21,76 . To learn whether genetic variations in the genes encoding for these proteins account for any of the variation in sensitivity of B-cells to PE seen in Fig.…”
Section: The Effect Of Caspase Mutations On the Sensitivity Of Human mentioning
confidence: 59%
“…It has previously been shown that PE exploits several host proteins for its binding to and entry into host cells 76 and initiates programmed cell death by inducing activities of host caspase-3, -6, and -7 21 . We investigated whether known (Fig.…”
Section: The Effect Of Caspase Mutations On the Sensitivity Of Human mentioning
confidence: 99%
See 1 more Smart Citation